2020
DOI: 10.1186/s40168-020-00943-5
|View full text |Cite
|
Sign up to set email alerts
|

Roundup causes embryonic development failure and alters metabolic pathways and gut microbiota functionality in non-target species

Abstract: Background Research around the weedkiller Roundup is among the most contentious of the twenty-first century. Scientists have provided inconclusive evidence that the weedkiller causes cancer and other life-threatening diseases, while industry-paid research reports that the weedkiller has no adverse effect on humans or animals. Much of the controversial evidence on Roundup is rooted in the approach used to determine safe use of chemicals, defined by outdated toxicity tests. We apply a system biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Concerning the quanti cation of CFU, GBH treatment showed a signi cant increase compared to CO. This effect could be related, among various factors, to host transcriptional changes enriched for lipid and carbon metabolism, as is suggested by Suppa et al (2020). Moreover, studies on dynamics of bacteria communities of the soil and rhizosphere, associated the increase of fast-growing bacteria abundance with the availability of carbon compounds in GLY presence (Imparato et al 2016).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Concerning the quanti cation of CFU, GBH treatment showed a signi cant increase compared to CO. This effect could be related, among various factors, to host transcriptional changes enriched for lipid and carbon metabolism, as is suggested by Suppa et al (2020). Moreover, studies on dynamics of bacteria communities of the soil and rhizosphere, associated the increase of fast-growing bacteria abundance with the availability of carbon compounds in GLY presence (Imparato et al 2016).…”
Section: Discussionmentioning
confidence: 81%
“…E. coli), decreased. GBHs have already been reported to disrupt the gut microbiota of animals likely to live near agricultural sites (i.e., bees, Motta et al 2018; water eas Daphnia spp., Suppa et al 2020). Besides, it was also found that GBH altered the diversity of the soil microbes (Wolmarans 2014) and can favors to certain species which perform less e ciently in the other conditions (Imparato et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by studies where gut microbiota dysbiosis was correlated to Hashimoto's thyroiditis (102)(103)(104), Graves' disease (104), thyroid cancer and thyroid nodules (105). In parallel in the field of toxicology, recent studies indicate that GBH is able to affect the intestinal microbiome of mice (106), rats (107)(108)(109)(110)(111)(112), honeybees (113,114), Japanese quails (115) and Daphnia magna (116). A possible explanation for this toxicity is that some classes of bacteria require the shikimate pathway (5enolpyruvylshikimate-3-phosphate synthase, EPSPS) for their metabolism.…”
Section: Future Perspectivesmentioning
confidence: 76%
“…Gly-induced GM alteration has been hypothesized to be related to neurological impairment such as autism spectrum disorders ( 78 , 79 ). Several studies showed that Gly can alter the abundances of gut microbial species both in vivo ( 57 , 58 , 80 82 ), in vitro ( 59 ), and also through bioinformatics tools ( 83 ). It has been estimated that more than half of species living in the central human GM are sensitive to Gly ( 84 ).…”
Section: Bidirectional Interaction Between Environmental Chemicals An...mentioning
confidence: 99%